Improvable Students in School Choice - Taylor Knipe; Josué Ortega (Queen's University Belfast, Queen's Business School, 2025)
The Deferred Acceptance algorithm (DA) frequently produces Pareto inefficient allocations in school choice problems. While a number of efficient mechanisms that Pareto-dominate DA are available, a normative question remains unexplored: which students should benefit from efficiency enhancements? We address it by introducing the concept of maximally improvable students, who benefit in every improvement over DA that includes as many students as possible in set-inclusion terms. We prove that common mechanisms such as Efficiency-Adjusted DA (EADA) and Top Trading Cycles applied to DA (DA+TTC) can fall significantly short of this benchmark. These mechanisms may only improve two maximally-improvable students when up to n - 1 could benefit. Addressing this limitation, we develop the Maximum Improvement over DA mechanism (MIDA), which generates an efficient allocation that maximises the number of students improved over DA. We show that MIDA can generate fewer blocking pairs than EADA and DA+TTC, demonstrating that its distributional improvements need not come at the cost of high justified envy.
Keywords: C78; D47; 330; school choice; improvable students